Retrofitting Heritage Building by Implementing Sustainability Concept in Malaysia - Lim , Keat Yee; Shukri, Sharyzee Mohmad; Bachek, Saiful Hazmi (MAJ - Malaysia Architectural Journal, 2020)
There are plenty of heritage buildings in Malaysia. Heritage buildings are normally very shabby yet historical, cultural value and aesthetic. Sustainability has a meaning of reducing the damage to environment and it is an environmentally friendly method to converse the environment. The aims of retrofitting heritage building by implementing sustainability concept are preserving the culture and history of heritage building and bringing a new vision to the building itself. Hence, retrofitting heritage building are encouraged to implement sustainability concept in Malaysia. For the reason that heritage buildings are mostly old, implementing sustainability concept to the building helps to extend building life somehow without damaging the culture of the building. Furthermore, sustainable design are encouraged to be implemented because it could bring benefits to environment such as slow down global warming, reduce emission, waste and pollution to the environment. Therefore, thermal, lighting and ventilation are the most important elements of sustainability which helps to improve the life of the building and surroundings. Sustainable design is a modern design in construction industry. Generation nowadays are not familiar with this concept even heritage building as well. Therefore, implementing sustainability concept to a heritage building are important because it will no longer extend to new generation. Sultan Abdul Samad Building is one of the heritage building in Malaysia. It is located on eastern side of Merdeka Square. The design of building was inspired by Moorish-style and it was built in 1897. The building was work for office purpose but it became a tourist attractions now. Moreover, implementing sustainability elements to building helps to diminish negative consequences on the environments and improve occupants health and comfort. It creates a better environment for new generation